'We call it the shaking illness': perceptions and experiences of Parkinson's disease in rural northern Tanzania - Dotchin Catherine L; Mshana Gerry; Walker Richard W (BMC, 2011)
Abstract Background Parkinson disease (PD) causes physical disability that negatively affects the quality of life of the sufferer's and their families. There are no Parkinson's disease (PD) social science studies published from Africa. This paper presents findings from a qualitative research study on how PD is perceived and treated in a population of approximately 161,000 within a demographic surveillance site in rural Tanzania. Methods We conducted in-depth interviews with 28 PD sufferers, 28 carers, 4 health workers and 2 traditional healers. In addition, 6 focus group discussions were conducted in 3 villages to investigate wider community views of PD. Results PD sufferers expressed frustration with the physical, psychological, social and economic consequences of the illness. Feelings of a diminished quality of life characterised by dependency, stigma and social isolation were common. Additionally, a handful of male sufferers related their sexual incompetence to the illness. Carers complained of lost income opportunities and social isolation resulting from caring for sufferers. Misconceptions about the cause, symptoms and appropriated PD treatment were widespread. Only 2 PD sufferers had commenced western type treatment through outsourcing drugs from other parts of the country and outside of Tanzania. Conclusions This study highlights the urgent need for PD awareness and treatment interventions in such settings. Such interventions need to address the concerns and needs of sufferers, their carers and the wider community, including the health care system.